Direct quantitation of the number of individual penicillin-binding proteins per cell in Escherichia coli. - Dougherty, T J (1996)
The penicillin-binding proteins (PBPs) are a set of enzymes that participate in the terminal stages of bacterial peptidoglycan assembly. As their name implies, these proteins also covalently bind and are inhibited by beta-lactam antibiotics. Although many studies have examined the relative binding affinities of a number of beta-lactam antibiotics, a surprisingly small number of studies have addressed the absolute numbers of each of the PBPs present in the bacterial cell. In the present study, the PBP values initially reported in Escherichia coli almost 20 years ago by B. G. Spratt (Eur. J. Biochem. 72:341-352, 1977) were refined. The individual PBPs from a known number of bacteria radiolabeled with [3H]benzylpenicillin were separated by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The radioactive bands were located, excised, and quantitatively extracted from the gel slices. The radioactivity was measured by scintillation counting, and the absolute disintegrations per minute were calculated. From the specific activity of the labeled penicillin, the absolute disintegrations per minute, and the CFU per milliliter, a determination of the number of each of the PBPs per cell was made. The measurements were performed on multiple samples to place statistical limits on the numbers obtained. The values for the individual PBPs found in E. coli deviated in several ways from the previously reported observations. Of particular significance is the higher number of molecules of PBP 2 and 3 observed, since these PBPs are known to participate in cell morphogenesis. The PBP content in both rich Luria broth medium and M9 minimal medium was determined, with the slower-growing cells in minimal medium possessing fewer of the individual PBPs per cell.